Key Directions of Japan's Economic Development (1950 – Present) - Zukhra, Hamdamova; Kamilova , M.Kh. (Journal of Macroeconomics and Social Development, 2024)
This article examines the impact of deflation on Japan's economy during a specific historical period. The author analyzes the consequences of deflation on various sectors of the economy, such as consumption, investments, exports, and more. Particular attention is paid to the measures taken by the government to overcome deflation. Throughout the article, the author highlights the significant challenges faced by the Japanese economy under prolonged deflation and discusses possible strategies for exiting this situation. By thoroughly analyzing Japan's history and experience, the author draws conclusions about how deflation can influence a country's economic development and what lessons can be learned from this experience for other countries. The main idea of the article is that deflation can have serious consequences for a country's economy and requires a comprehensive approach from both the government and the business community to mitigate its negative effects.